The determinants of international mobility of students - Michel Beine; Romain Noël; Lionel Ragot (Center for Economic Studies and ifo Institute (CESifo), 2012)
This paper analyzes the determinants of the choice of location of international students. Building on the documented trends in international migration of students, we develop a small theoretical model allowing to identify the various factors associated to the attraction of migrants as well as the costs of moving abroad. Using new data capturing the number of students from a large set of origin countries studying in a set of 13 OECD countries, we assess the importance of the various factors identified in the theory. We find support for a significant network effect in the migration of students, a result so far undocumented in the literature. We also find a significant role for cost factors such as housing prices and for attractiveness variables such as the reported quality of universities. In contrast, we do not find an important role for registration fees.
Keywords: F22; O15; 330; student mobility; network effect; migration costs; higher education policy; Studierende; Internationale Wanderung; Auslandsaufenthalt; Wohnstandortwahl; Soziales Netzwerk; OECD-Staaten